Laboratory validation of seismic damage assessment in reinforced soil models based on sensor-enabled piezoelectric geogrids (SPGG) - Wang, Jun; Xiang, Zhiqiang; Fu, Hongtao; Rao, Yu; Gao, Ziyang; Ni, Junfeng (Geotextiles and geomembranes, 2025)
Earthquakes are common geological disasters, and slopes under seismic loading can trigger coseismic landslides, while also becoming unstable due to accumulated damage caused by the seismic activity. Reinforced soil slopes are widely used as seismic-resistant geotechnical systems. However, traditional geosynthetics cannot sense internal damage in reinforced soil systems, and existing in-situ distributed monitoring technologies are not suitable for seismic conditions, thus limiting accurate post-earthquake stability assessments of slopes. This study presents, for the first time, the use of a batch molding process to fabricate self-sensing piezoelectric geogrids (SPGG) for distributed monitoring of soil behavior under seismic conditions. The SPGG's reinforcement and damage sensing abilities were verified through model experiments. Results show that SPGG significantly enhances soil seismic resistance and can detect soil failure locations through voltage distortions. Additionally, the tensile deformation of the reinforcement material can be quantified with sub-centimeter precision by tracking impedance changes, enabling high-precision distributed monitoring of reinforced soil under seismic conditions. Notably, when integrated with wireless transmission technology, the SPGG-based monitoring system offers a promising solution for real-time monitoring and early warning in road infrastructure, where rapid detection and response to seismic hazards are critical for mitigating catastrophic outcomes. •This study introduces sensor-enabled piezoelectric geogrids (SPGGs) designed for distributed monitoring of reinforced soil structures under seismic conditions.•A batch fabrication process was developed, enabling the rapid and scalable production of SPGG with enhanced consistency and reliability.•Model tests demonstrated that SPGG significantly improves the seismic resistance of reinforced soil while providing real-time monitoring capabilities.•The SPGG system can identify internal failure locations through voltage distortion and quantify geogrid deformation with millimeter-level precision using impedance variations.The findings highlight the strong potential of SPGG for non-destructive monitoring of slope stability and post-earthquake hazard assessment, offering a novel approach to geotechnical disaster prevention.